2021
DOI: 10.1210/endocr/bqab092
|View full text |Cite
|
Sign up to set email alerts
|

FGF21 Normalizes Plasma Glucose in Mouse Models of Type 1 Diabetes and Insulin Receptor Dysfunction

Abstract: Fibroblast growth factor 21 (FGF21) is a member of the fibroblast growth factor (FGF) family of proteins. The biological activity of FGF21 was first shown to induce insulin independent glucose uptake in adipocytes through the GLUT1 transporter. Subsequently, it was shown to have effects on the liver to increase fatty acid oxidation. FGF21 treatment provides beneficial metabolic effects in both animal models and patients with obesity, type 2 diabetes mellitus (T2D) and/or fatty liver disease. In this paper, we … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 23 publications
1
5
0
Order By: Relevance
“…In the cardiovascular system, FGF21 exerts a protective function on endothelial cells by resisting oxidative stress, inhibiting aberrant vascular remodeling, and antagonizing angiotensin II [ 47 , 48 , 49 , 50 ]. Studies have demonstrated that FGF21 can also significantly reduce fasting blood glucose level and improve glucose clearance without hypoglycemia [ 51 , 52 , 53 , 54 ]. Significant FGF21 production in the liver and enhanced circulating FGF21 may, therefore, contribute to the beneficial effects of PEM.…”
Section: Discussionmentioning
confidence: 99%
“…In the cardiovascular system, FGF21 exerts a protective function on endothelial cells by resisting oxidative stress, inhibiting aberrant vascular remodeling, and antagonizing angiotensin II [ 47 , 48 , 49 , 50 ]. Studies have demonstrated that FGF21 can also significantly reduce fasting blood glucose level and improve glucose clearance without hypoglycemia [ 51 , 52 , 53 , 54 ]. Significant FGF21 production in the liver and enhanced circulating FGF21 may, therefore, contribute to the beneficial effects of PEM.…”
Section: Discussionmentioning
confidence: 99%
“…GEP44-mediated increases in glucose transport also correlated with its stimulation of lactate production and thus a downstream impact on muscle metabolism; however, Y1-R agonism may also stimulate a reaction step in the glycolytic pathway. Given that previous findings suggested a role for insulin-independent glucose uptake in pathways leading to glucose homeostasis (Wiernsperger 2005, Diener, Mowbray et al 2021, the contributions of Y1-R may be physiologically significant. As GEP44 acts directly on muscle tissue, while its effects on islets require concomitant Y1-R antagonism, activation of Y1-R expressed in muscle tissue may ultimately prove to be a critical factor in reducing serum glucose levels, alongside any potential effects on insulin secretion and glucagon release.…”
Section: Y1-r-mediated Effects On Pancreatic Isletsmentioning
confidence: 97%
“…In streptozotocin‐treated mice, a model of type 1 diabetes (T1D), treatment with a polyethylene glycol‐conjugated (PEG) and half‐life extended form of FGF21 (FGF21–PEG) normalized plasma glucose, without restoring pancreatic β‐cell function. FGF21–PEG also normalized plasma glucose levels and improved glucose tolerance in mice chronically treated with a competitive insulin receptor antagonist, a model of autoimmune/Type‐B insulin resistance (Diener et al, 2021). In obese cynomolgus monkeys and overweight/obese humans with T2D, administration of a long‐acting FGF21 analog, PF‐05231023, decreased food intake resulting in a significant decrease in body weight and improved plasma lipoprotein profile, without significant effects on glycemic control (Huang et al, 2013; Talukdar, Zhou, et al, 2016).…”
Section: Fgf Signaling and Metabolic Diseasementioning
confidence: 99%